Preparing for next-generation information warfare with generative AI - Eleonore Pauwels (Centre for International Governance Innovation (CIGI), 2024)
AI is making information warfare more powerful and more accessible. Generative AI combined with data capture provides new techniques to industrialize the offensive use of disinformation. In addition, the integration of generative AI with other powerful technologies complexifies the potential of information warfare. What is at stake is the weaponization of dual-use knowledge itself. Generative AI is already learning to democratize military and civilian expertise in technological domains as complex as AI, neuro-, nano- and biotechnology. Such capacity will provide both state and non-state actors with access to knowledge and mentorship related to impactful technologies. This diffusion of power will change the nature of information and physical warfare, increasing dual-use knowledge asymmetries between threat actors in conflicts. There is an urgent need to prepare for misuse scenarios that harness technological convergence. New converging risks will bring collective security challenges that are not well understood or anticipated globally.
Keywords: 330